Inhibition studies of Helicobacter pylori urease with Schiff base copper(ii) complexes. Issue 20 (9th February 2016) - You, Zhonglu; Liu, Mingyang; Wang, Cunfang; Sheng, Guihua; Zhao, Xinlu; Qu, Dan; Niu, Fang
Abstract : Nine new copper(ii ) complexes derived from various Schiff bases were prepared. Five complexes show effective urease inhibitory activities. Complex5 has the most effective activity against urease, with a mixed competitive inhibition mechanism. Abstract : Nine new copper(ii ) complexes derived from various Schiff bases were prepared. They are [Cu2 Br2 (L 1 )2 ] (1 ), [Cu(L 2 )2 ]·2NO3 ·2CH3 OH (2 ), [Cu(L 3 )2 ]·2Br (3 ), [Cu(L 4 )2 ] (4 ), [Cu2 Cl4 (L 2 )2 ] (5 ), [Cu2 Cl2 (L 5 )2 ] (6 ), [CuL 6 (NCS)] (7 ), [CuClL 6 ]·CH3 OH (8 ), and [Cu2 (L 7 )2 ] (9 ), where L 1 is the monoanionic form of 2-chloro- N ′-(4-diethylamino-2-hydroxybenzylidene)benzohydrazide (HL 1 ), L 2 is the zwitterionic form of 4-methyl-2-((3-morpholinopropylimino)methyl)phenol (L 2 ), L 3 is the zwitterionic form of 2-bromo-4-chloro-6-((2-(2-hydroxyethylamino)ethylimino)methyl)phenol (L 3 ), L 4 is the monoanionic form of 2-bromo-4-chloro-6-((cyclopentylimino)methyl)phenol (HL 4 ), L 5 is the monoanionic form of 2-((cyclopropylimino)methyl)-4-methylphenol (HL 5 ), L 6 is the monoanionic form of 4-methyl-2-((pyridin-2-ylmethylimino)methyl)phenol (HL 6 ), and L 7 is the dianionic form of N, N ′-bis(5-methylsalicylidene)-1, 4-diiminobutane (H2 L 7 ). The complexes were characterized by infrared and UV-Vis spectra, and single crystal X-ray diffraction. The Cu atoms in complex1 display square pyramidal coordination, in complex5 display trigonal bipyramidal coordination, in complex9 show tetrahedrally distorted square planar coordination, and in the remaining complexes display square planar coordination. Complexes2, 3, 5, 7 and8 show effective urease inhibitory activities, with IC50 values of 0.37 ± 1.22, 0.21 ± 0.97, 0.03 ± 0.78, 0.39 ± 0.58 and 0.76 ± 0.95 μM, respectively. Molecular docking study of the complexes with Helicobacter pylori urease was performed. Complex5 has the most effective activity against urease, with a mixed competitive inhibition mechanism. The complex interacts with the nickel atom of the urease active center, and with the remaining parts of the complex molecule block the entrance of the urease active pocket.